Water lever measure and control using ultrasonic sensor - Abdul Hafiz, Mohd Idzhan (2016)
In recent years, natural disaster specifically flash flood have frequently caused major properties damage and life casualty, due to unconscious of rapid water level rising in the flood prone area. A water level monitoring system, is a crucial component that can prevent the unawareness during monsoon season, a real-time alerting system equipped with range sensor and audio visual mechanism possibly will be the solution for this problem. This project proposed an idea for the application for public interest to measure the escalation of water level by using ultrasonic sensor. The sensor is placed vertically to the lateral water surface connected to the ultrasonic sensor controlled by microcontroller to measure the distance of the water. Whenever the water reach certain level, the ultrasonic sensor will transmit the signal and the level is calculated using an appropriate formula.